Digital Transformation in Indonesian Religious Education: A Case Study of Madrasah Management at Kemenag Sleman - Diah Khoirohnissah (Journal of Islamic Education Management Research, 2023)
Purpose – The purpose of this study is to analyze comprehensively the impact of digital transformation on the data processing system within the Madrasah Education section at the Ministry of Religious Affairs (Kemenag) in Sleman district, Indonesia. It focuses on assessing how digital transformation enhances efficiency, accuracy, and connectivity in managing crucial educational data. Design/methods– The research employed a qualitative methodology, emphasizing descriptive analysis to explore the integration of digital technologies into the management practices of religious education institutions. Data collection combined structured interviews with key educational figures and an extensive review of relevant documents and digital artifacts, including policy documents, implementation reports, and analytics from digital platforms such as EMIS, SIMPATIKA, SIMSARPRAS, and SEDAKEP. Findings – The study uncovered that digital transformation significantly improves the management of educational data, enhancing efficiency, accuracy, and connectivity within the Madrasah Education section of Kemenag Sleman. Through the deployment of digital tools and platforms, the institution has seen substantial advancements in its operational capabilities, reflecting a broader trend towards digitalization in educational management. Research implications/limitations – This research contributes to the understanding of digital transformation in the educational sector, particularly within settings where cultural and religious factors are prominent. However, its focus on a single institution within a specific cultural and administrative context may limit the generalizability of the findings. Future studies are encouraged to explore digital transformation across various educational environments and cultures. Practical implications – The findings offer valuable insights for policymakers, educators, and administrators in religious education institutions considering or undergoing digital transformation. Strategic planning and stakeholder engagement are emphasized as crucial for the successful implementation of digital tools in educational settings. Originality/value –This study provides a unique contribution to the literature by examining digital transformation in the context of Indonesian religious education, a sector where digital adoption intersects significantly with cultural and religious considerations. It highlights the potential of digital strategies to revolutionize traditional educational management practices, offering a model for similar institutions navigating the digital era.